Profil Fingerprinting Populasi Etnis Sumba Barat Daya pada Mahasiswa IKIP Budi Utomo - Naomi Nodu Madi; Nikmatul Iza; Khoirun Nisa (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
Fingerprints as evidence of very important material are believed to have unique and distinctive properties in the sense that no two individuals have the exact same fingerprint pattern, even identical twins have different fingerprint patterns. A person's fingerprint will not change for a lifetime. The objectives to be achieved in this study are to identify and identify the dominant fingerprint pattern in the ethnic population of Southwest Sumba, the students of IKIP Budi Utomo Malang.This type of research is a descriptive study with a qualitative approach to identify the fingerprinting profile of the ethnic population of Southwest Sumba, the students of IKIP Budi Utomo Malang. The fingerprint samples taken will be analyzed at the IKIP Budi Utomo Malang campus. The identification results in the fingerprinting profile study of the Southwest Sumba ethnic population, the students of IKIP Budi Utomo Malang showed that the dominant general pattern was the Loop pattern with a percentage of 55.0% or 385 fingers, the second dominant pattern was the whorl pattern with a percentage of 42.29% or 229 fingers. While the first dominant sub-unit pattern is the Ulnar Loop pattern with a percentage of 52.71% or 369 fingers and the second dominant pattern is the Plain Whorl pattern with a percentage of 32.71% or 229 fingers.